(untitled) (INNOVATIVE ECONOMY, 2024)
Honcharenko I.V. SOCIAL INFRASTRUCTURE OF RURAL AREAS IN THE REGION IN THE CONTEXT OF SMART SPECIALIZATION STRATEGY IMPLEMENTATION Purpose. The aim of the article is to summarize the issues of social infrastructure in rural areas of the region and to develop strategies for their resolution. Methodology of research. The study utilized statistical observations and empirical research conducted in rural communities of the Mykolaiv region. Statistical data included official reports provided by local authorities. Empirical research is based on field studies, content analysis of media sources, and observations. The collected data are processed to identify key trends and interrelations, forming the basis for recommendations to improve living conditions and develop local social infrastructure. Findings. The study analyzed the main problems of social infrastructure in rural areas of the region. Identified issues include insufficient access to quality education, a shortage of medical personnel, lack of centralized water supply, inadequate waste management, destruction of cultural assets, and energy supply problems. It was also revealed that the current situation exhibits signs of infrastructural violence against the rural population of the Mykolaiv region, leading to social and economic isolation and migration to cities or abroad. Directions for infrastructure modernization were developed, including the implementation of innovative technologies in healthcare services, energy efficiency, transport accessibility, education, and waste management. Efforts to develop rural areas should focus on cooperation with universities and international organizations, as well as leveraging mobility and remote work. Originality. The feasibility of innovative SMART development of the social infrastructure in rural areas of the Mykolaiv region is substantiated. This approach involves the use of technological solutions to improve the quality of life, access to social services, and economic development in resource-constrained conditions. It is found that this approach will help maintain the attractiveness of rural areas for residents and attract qualified personnel to work at innovative facilities. Practical value. Specific recommendations for the innovative development of social infrastructure in rural areas of the region are developed. The application of the research results will contribute to improving the quality of life, reducing social inequality and strengthening the resilience of the region. Key words: social infrastructure, rural areas, communities, SMART development, population, potential, innovations.